Some Problematic Philosophical Implications of the Thomas Theorem - Aleksandrowicz, Dariusz (Practica et Speculativa: Studies Offered to Professor Andrzej M. Kaniowski, 2022)
Despite of its wide recognition in the social sciences, the Thomas theorem lacks clarity and finds its expression in diverging statements. A sound core of the theorem is blurred by notions these statements consist of. They include untenable ontology and epistemology along with a flawed claim concerning the peculiarity of the human world.